2018
DOI: 10.1097/pts.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Resident Safety Culture in Six Nursing Homes in Belgium

Abstract: Objectives: The primary aim was to measure resident safety culture in six nursing homes in northern Belgium (Flanders). In addition, differences in safety culture perceptions between professions were also examined. Finally, results of the present study were compared with the Nursing Home Comparative Database from the Agency for Healthcare Research and Quality (USA).Methods: A cross-sectional study was conducted by administering the Nursing Home Survey on Patient Safety Culture in six nursing homes in Belgium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 40 publications
7
22
4
4
Order By: Relevance
“…and 'compliance with procedures' dimensions are the priority areas to be improved in nursing homes, as they had the lowest scores and the lowest PRRs. A similar situation was found in other countries, such as the USA (Smith et al, 2018), Belgium (Desmedt et al, 2018) and Norway (Ree & Wiig, 2019). The majority of staff are reported to be under-educated, lack experience and are only temporarily employed, which was confirmed in a similar study (Yang et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…and 'compliance with procedures' dimensions are the priority areas to be improved in nursing homes, as they had the lowest scores and the lowest PRRs. A similar situation was found in other countries, such as the USA (Smith et al, 2018), Belgium (Desmedt et al, 2018) and Norway (Ree & Wiig, 2019). The majority of staff are reported to be under-educated, lack experience and are only temporarily employed, which was confirmed in a similar study (Yang et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…The majority of the literature on patient safety culture has focused on hospital settings, with relatively few studies conducted in nursing homes (Gartshore et al., 2017; Weaver et al., 2013). Quantitative surveys have been used in most studies conducted in the long‐term care facilities (Abusalem et al., 2019) or nursing homes (Desmedt, Petrovic, Beuckelaere, & Vandijck, 2018; Lin, Tseng, Hsu, Chiang, & Tseng, 2017; Ree & Wiig, 2019; Titlestad, Haugstvedt, Igland, & Graue, 2018). A few studies have reported on the relationship between patient safety culture and adverse events in nursing homes (Gartshore et al., 2017; Weaver et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings highlight fragile and moderate areas on the resident safety culture of nursing homes, such as compliance with procedures, nonpunitive response to mistakes, and staffing. In our sample, the composite average positive percent for compliance with procedures (51%) and nonpunitive response to mistakes (55%) were lower than those for nursing homes in Belgium (50% and 61%) [47] and Norway (62% and 71%) [48]. Conversely, the composite average positive percent for staff was greater in our sample (60%) relative to those nursing homes in Belgium (38%) and Norwegian (44%) studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Conversely, the composite average positive percent for staff was greater in our sample (60%) relative to those nursing homes in Belgium (38%) and Norwegian (44%) studies. In addition, top average positive composites in our sample -teamwork (78%) and, training and skills (70%) -were greater than those reported in [47] (76% and 65%) and [48] (68% and 51%). These indicators could be used to benchmark and steer where nursing home improvement initiatives are needed the most.…”
Section: Discussioncontrasting
confidence: 52%
“…Nos últimos anos houve um grande desenvolvimento de estudos acerca da CSP nas ERPI (Gartshore, Waring & Timmons, 2017). Impulsionados pelos EUA, outros países europeus e asiáticos têm desenvolvido estudos que permitem extrair uma razoável perspetiva no âmbito a CSP nas estruturas para pessoas idosas (Bondevik, Hofoss, Husebø & Deilkås, 2017;Santos, 2015;Park, Hong, Lim & Lee, 2015;He et al, 2020;Desmedt, Petrovic, Beuckelaere & Vandijck, 2018).…”
Section: Discussionunclassified